Frugivory and seed dispersal effectiveness in two Miconia (Melastomataceae) species from ferruginous campo rupestre - Santos, Alessandra M. O.; Jacobi, Claudia M.; Silveira, Fernando A. O. (Seed science research, 2017)
Seed dispersal effectiveness (SDE) is a useful framework to explore the evolutionary and ecological consequences of seed dispersal to plant fitness. However, SDE is poorly studied in tropical open grasslands. Here, we studied both quantitative and qualitative components of SDE in two species of Miconia (Melastomataceae) from ferruginous campo rupestre, a vegetation highly threatened by mining activities. We determined fruit traits and fruit availability and found that fruits of both species are produced in times of resource scarcity at the study site. Based on the number of visits and the number of fruits removed per visit, we calculated the quantitative component of SDE for both species. Finally, we explored the qualitative component of SDE by means of a controlled experiment that simulated the effects of gut passage on seed germination. Bird species differed strongly in the quantitative component of SDE. Gut passage did not affect germination compared with hand-extracted seeds, except for a minor negative effect on germination time in M. pepericarpa. However, seeds within intact fruits showed lower germination percentages compared with hand-extracted seeds. Our data indicate that Miconia species from ferruginous campo rupestre are visited by a diverse assemblage of generalist birds that differ in quantitative, but not qualitative, seed dispersal effectiveness. We argue that planting Miconia species can overcome seed limitation in degraded areas and thus assist ecological restoration after mining abandonment.